Determinants of intravaginal practices among HIV-infected women in Zambia using conjoint analysis. (May 2016) - Alcaide, Maria L; Cook, Ryan; Chisembele, Maureen; Malupande, Emeria; Jones, Deborah L
Intravaginal practices (IVPs) are associated with an increased risk of bacterial vaginosis and may play a role in HIV transmission. The objective of this study was to identify the importance of factors underlying the decision to engage in IVP using conjoint analysis; a novel statistical technique used to quantify health-related decisions. This study was a cross-sectional study. HIV-infected women in Zambia completed audio computer-administered self-interview questionnaires assessing demographic, risk factors and IVPs. Reasons for engaging in IVPs were explored using conjoint questionnaires. Conjoint analysis was used to identify the relative importance of factors for engaging in IVPs. Results of the conjoint analysis demonstrated that hygiene was the most important reason for engaging in IVPs (mean importance score = 61, SD = 24.3) followed by partner's preference (mean importance score = 20, SD = 14.4) and health (mean importance score = 17, SD = 13.5). When making the decision to engage in IVPs, women rank the importance of hygiene, partner preference and health differently, according to their personal characteristics. The use of conjoint analysis to define the characteristics of women more likely to engage in specific practices should be used to develop tailored rather than standardised IVP interventions, and such interventions should be incorporated into clinical practice and women's health programmes.